The influence of product price and quality on customer loyalty with customer satisfaction as an intervening variable at PT. Brother Group, Medan - Sherly Ogestine; Efendy Pakpahan; Cut Fitri Rostina (Journal of Economics and Business Letters, 2023)
The increasing number of competitors forces companies to be more competitive in their actions and decision-making in marketing their products or services. Customer loyalty becomes the target of every company so that the company can survive and grow in the market. Product quality and product prices certainly have an influence on customer satisfaction and customer loyalty. The purpose of this research is to determine the influence of product prices and product quality on customer satisfaction and customer loyalty, and whether there is a correlation between customer satisfaction and customer loyalty. In conducting the research, the researcher used primary data obtained from questionnaires distributed to the customers of PT. Brother Group, Medan. The number of respondents used was 92. This primary data was processed using the statistical software SPSS 22. Tests conducted included validity tests, reliability tests, classic assumption tests such as normality tests, multicollinearity tests, and heteroscedasticity tests, followed by path analysis then hypothesis tests which include partial tests, determination tests, and also Sobel tests. In this study, price was coded as (x1), product quality as (x2), customer satisfaction as (Z), and customer loyalty as (Y). The results obtained in this study show that x1 has a significant effect on Y with a t-count value of 2.615 > t-table 1.661. x2 does not have a significant effect on Y with a t-count value of 0.788 < t-table 1.661. x1 has a significant effect on Z, with a t-count value of 5.243 > t-table 1.661, x2 has a significant effect on Z with a t-count value of 3.314 > t-table 1.661, Z has a significant effect on Y with a t-count value of 6.222 > t-table which is 1.661, x1 has an effect on Y with Z as an intervening variable with a t-count value of 3.941633 > t-table value of 1.661, x2 has an effect on Y with Z as an intervening variable with a t-count value of 2.930647902 > t-table value of 1.661.